Penerapan Sistem Profit Pada Pembiayaan KPR Subsidi Di BTN Syariah Kota Semarang - Fira Adelia Nur Chalizah; Ana Silviana (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2023)
AbstractDecree of the Minister of Public Works and Public Housing No. 242/KPTS/M/2020 sets the interest rate/margin in KPR subsidized financing at 5%, BTN Syariah as the implementing bank also complies with this. The problem that arises is how to use the interest system for subsidized mortgage financing at the BTN Syariah Semarang City and whether the subsidized mortgage financing is in accordance with Islamic law. This study aims to provide an explanation of the interest system in Islamic banks in mortgage financing. This study uses a Social Legal approach with a descriptive analytical research specification. The results obtained from this study are that BTN Syariah does not use an interest system in its financing, the profits obtained are only based on margins and subsidized mortgages at BTN Syariah have been based on the DSN MUI fatwa and are declared permissible to be implemented.Keywords: financing; KPR subsidy; BTN syariahAbstrakKeputusan Menteri Pekerjaan Umum dan Perumahan Rakyat No. 242/KPTS/M/2020 menetapkan suku bunga/marjin dalam pembiayaan KPR Subsidi sebesar 5%, BTN Syariah sebagai bank pelaksana juga mematuhi hal tersebut. Permasalahan yang timbul adalah bagaimana penggunaan sistem bunga pada pembiayaan KPR Subsidi di BTN Syariah Kantor Cabang Kota Semarang dan apakah pembiayaan KPR Subsidi sudah sesuai dengan syariat Islam. Penelitian ini bertujuan memberikan penjelasan mengenai sistem bunga pada bank syariah dalam pembiayaan KPR. Penelitian ini menggunakan metode pendekatan Social Legal dengan spesifikasi penelitian bersifat deskriptif analitis. Hasil yang diperoleh dari penelitian ini adalah BTN Syariah tidak menggunakan sistem bunga pada pembiayaannya, keuntungan yang diperoleh hanya berdasarkan marjin dan KPR subsidi pada BTN Syariah telah berdasarkan fatwa DSN MUI dan dinyatakan diperbolehkan untuk dilaksanakan.Kata kunci: pembiayaan; KPR subsidi; BTN syariah